A systemic approach to leveraging student engagement in collaborative learning to improve online engineering education. (2019) - Qiu, Robin G.
Online higher education is transformative and quite different from residential college education. Lacking effective and consistent pedagogical engagement has been criticised for a high drop-out rate in the online education in general. This study aims to find a solution to facilitate learning engagement in an online engineering education setting. By relying on the known knowledge in the pedagogies of engagement in college education, this paper proposes a systemic framework for promoting positive online students' learning engagement. Different from empirical studies of conducting hypothesis tests, we show a practical and model-driven approach to assessing and enhancing problem-based collaborative teaching/learning practices. The proposed framework is explored through both a pilot test and a confirming test. Rules of thumb are identified and generalised, which could be used to help students/instructors retune their collaborative practices in a proactive manner for retaining positive and effective learning engagement in an online engineering education setting.